2020
DOI: 10.1002/joc.6719
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term variability and trends in meteorological droughts in Western Europe (1851–2018)

Abstract: We analysed long-term variability and trends in meteorological droughts across Western Europe using the Standardized Precipitation Index (SPI). Precipitation data from 199 stations spanning the period 1851-2018 were employed, following homogenisation, to derive SPI-3 and SPI-12 series for each station, together with indices on drought duration and severity. Results reveal a general absence of statistically significant long-term trends in the study domain, with the exception of significant trends at some statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 103 publications
(140 reference statements)
2
56
0
1
Order By: Relevance
“…The increase in the number of CHD events over the south-eastern part of Europe is mainly due to an increase both in the duration of heatwaves over this region (Figure 3A) as well as in the frequency of the HW events (Figure 3B). Overall, August SPI3 indicates an overall wetting over the northern part of Europe and a drying tendency over the southern part of Europe (Figure 3C), which is in agreement with previous studies regarding the change in the occurrence of drought events over Europe, based on the SPI drought index Vicente-Serrano et al, 2021).…”
Section: Historical Evolution Of Compound Events (Hot and Dry)supporting
confidence: 92%
“…The increase in the number of CHD events over the south-eastern part of Europe is mainly due to an increase both in the duration of heatwaves over this region (Figure 3A) as well as in the frequency of the HW events (Figure 3B). Overall, August SPI3 indicates an overall wetting over the northern part of Europe and a drying tendency over the southern part of Europe (Figure 3C), which is in agreement with previous studies regarding the change in the occurrence of drought events over Europe, based on the SPI drought index Vicente-Serrano et al, 2021).…”
Section: Historical Evolution Of Compound Events (Hot and Dry)supporting
confidence: 92%
“…Both indices are very similar, with the Pearson correlation coefficient between them being ρ = 0.99, and both match the same dry periods. This indicates that the contribution of precipitation deficits to the drought severity in the BRB prevails over the temperature excess, unlike other regions, such as the Mediterranean region, where the increase in the atmospheric evaporative demand driven by increasing temperatures in the last decades has enhanced droughts, independently of the precipitation evolution in the region [49,50]. In fact, the link between droughts and heat waves is widely known: high temperatures accelerate soil drying and dry soils in turn warm the atmosphere by retaining less water for evapotranspiration [51].…”
Section: Drought Characteristics During the Period Of 1980-2017mentioning
confidence: 99%
“…Raso (1993) stressed the severity of the drought periods identified at the beginning of the twentieth century, but also heavy droughts in 1949-1950(Esteban-Parra et al, 1998Olcina, 1994), the beginning of the 1980s (Pérez Cueva, 1983;Raso et al, 1981), but also between 1990and 1995(Vicente-Serrano, 2013. More recent studies suggest that an examination of precipitation series has not found any drought trends since at least 1870 (Coll et al, 2017;Vicente-Serrano et al, 2020b). An analysis based on high spatial resolution drought datasets has shown no relevant trends in drought magnitude and duration since 1961 (Domínguez-Castro et al, 2019b).…”
Section: The Study Of Drought Variability and Trendsmentioning
confidence: 99%
“…Over the last decade, Spanish researchers have studied drought variability and trends in other regions of the world, including global analysis (Vicente-Serrano et al, 2017b), studies on a European level (Serra et al, 2014;Vicente-Serrano et al, 2020b), in other European countries like Portugal (Santos et al, 2010) and Italy (Baronetti et al, 2020), and in other areas, including Syria (Mathbout et al, 2018), Iran (Karimi et al, 2020), Bolivia (Maillard et al, 2020;Vicente-Serrano et al, 2015b), Ethiopia (El Kenawy et al, 2016, Oman (El Kenawy et al, 2020), Mexico (Serrano-Barrios et al, 2016, and Vietnam (Stojanovic et al, 2020).…”
Section: The Study Of Drought Variability and Trendsmentioning
confidence: 99%